LA INFLUENCIA DE LA PSICOLOGÍA EN EL DESARROLLO EMPRESARIAL - Rosero, Diego; Núñez, Ángela; Núñez, Isaac; López , Carmita (Revista Inclusiones, 2019)
Currently the world is facing various commercial conflicts including unfair competition, unemployment, so it is necessary to consider the emotional state of its employees within business organizations; it is necessary to take into account their development in the productive sector and their results that they leave to companies. What is reflected and manifested, that the greater achievement of meeting goals better meets the proposed objectives. The mood, the emotions, the behavior of each of the collaborators, the relationship with the co-workers are analyzed, the family relationship is controlled, because if there is peace in the home, they can concentrate on their assigned tasks, the performance exceeds all sacrifice and all effort. There will be no concentration, distraction, or worry. The objective of this research is to create positive changes within companies, taking care of the emotional part of the collaborators in order to make the most of the workforce. The methodology applied was an analysis of the influence of the application of sychology on the emotions of workers and their business productivity, the survey was applied to 50 people of the company, both the employer and the employees to define what the problems within the organization are. The main results are that 72% of the surveyed population considers that the company is concerned about their emotional state and the involvement of their family problems and psychological development within the company, 24% considered partially well, 4% considered good, becoming problematic partners, without productivity